High Adherence to System‐Level Performance Measures for Rheumatoid Arthritis in a National Early Arthritis Cohort Over Eight Years. Issue 6 (25th March 2018) - Barber, Claire E. H.; Schieir, Orit; Lacaille, Diane; Marshall, Deborah A.; Barnabe, Cheryl; Hazlewood, Glen; Thorne, J. Carter; Ahluwalia, Vandana; Bartlett, Susan J.; Boire, Gilles; Haraoui, Boulos; Hitchon, Carol; et al.
Abstract : Objective: To assess adherence to 3 system‐level performance measures in a national early rheumatoid arthritis (RA) cohort. Methods: Patients enrolled in the Canadian Early Arthritis Cohort (2007–2015) who met 1987 or 2010 American College of Rheumatology/European League Against Rheumatism criteria with <1 year of symptom duration and ≥1 year of followup after enrollment were included. Performance measures assessed were the percentage of RA patients seen in yearly followup, and the number of gaps between visits of >12 or >14 months, the percentage of RA patients treated with a disease‐modifying antirheumatic drug (DMARD), and days from RA diagnosis to initiation of a DMARD. Results are shown stratified by enrollment year to assess for temporal changes in performance. Results: A total of 1, 763 early RA patients were included (mean age 54 years, 73% female, and 82% white). At enrollment, mean ± SD disease duration was 6 ± 3 months, and Disease Activity Score in 28 joints was 5.1 ± 1.5. Over 8 years, the proportion of patients seen in annual followup declined from 100% to 91%. Over followup, 42% of patients had 0 gaps in care of >12 months, and 64% had 0 gaps >14 months. The percentage of DMARD‐treated early RA patients was and remained high (95–87%), and the percentage receiving DMARDs within 14 days of diagnosis was 75%. Median time‐to‐DMARD therapy was 1 day, indicating DMARDs were initiated at diagnosis (90th percentile 93 days). Conclusion: There was evidence of high adherence to system‐level performance measures in this early RA cohort following a protocol. Small declines in performance were noted with increasing length of patient followup. Our findings are useful for performance measure benchmarking.